2018
DOI: 10.4103/ijem.ijem_473_17
|View full text |Cite
|
Sign up to set email alerts
|

Duration of casual sunlight exposure necessary for adequate Vitamin D status in Indian Men

Abstract: Objectives:To investigate the duration of casual sunlight ultraviolet-B (UVB) exposure required to maintain optimal Vitamin D status (25-hydroxyvitamin-D [25(OH)D]) >50 nmol/L in urban Indian men, using polysulfone (PSU) dosimeters and a sunlight exposure questionnaire.Methods:In healthy men (aged 40–60 years) from Pune (18.52° N, 73.86° E), India, serum 25(OH)D was measured using enzyme-linked immunosorbent assay. Sunlight exposure was assessed using PSU dosimeter and by questionnaire.Results:Of 160 men (48.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…We found that the serum 25(OH)D concentrations increased approximately 10% within 1 week of UVB exposures, confirming that exposing the skin to NB-UVB light is an effective way to increase vitamin D serum levels (Osmancevic et al, 2015). It has previously been shown that the relationship between vitamin D production in the skin and UVB light exposure is not linear, but rather plateaus when serum levels reach the vitamin D sufficiency range (Jamil et al, 2018; Patwardhan et al, 2018). We found that the newly synthesized vitamin D is dependent on the preexisting serum 25(OH)D concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the serum 25(OH)D concentrations increased approximately 10% within 1 week of UVB exposures, confirming that exposing the skin to NB-UVB light is an effective way to increase vitamin D serum levels (Osmancevic et al, 2015). It has previously been shown that the relationship between vitamin D production in the skin and UVB light exposure is not linear, but rather plateaus when serum levels reach the vitamin D sufficiency range (Jamil et al, 2018; Patwardhan et al, 2018). We found that the newly synthesized vitamin D is dependent on the preexisting serum 25(OH)D concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The limited availability of vitamin D from dietary sources ensures that in humans, 80% of their vitamin D requirements need to be met through exposure to Ultraviolet B (UVB) light (Holick, 2002; Patwardhan et al, 2018). UVB light (light emitted wavelengths between 280 and 315 nm) produces vitamin D in the skin through the conversion of the cholesterol derivative 7-dehydrocholesterol, resulting in an increase in serum levels of 25(OH)D, the biological inactive form of vitamin D. Sun avoidance, dwelling far away from the equator, and lifestyle are some of the factors that limit exposure to UVB light on a regular basis (Lu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…At least 25% of skin surface has to be exposed. UVB can’t penetrate glass windows and there is no overdose of Vitamin D from overexposure to sunlight [ 26 ]. However, in the current study, only half of the HCWs identified sunlight exposure as the most common source of vitamin D. The rest of them indicated sources other than sunlight.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that going outdoors in the sun for greater than 60 min per day is required for maintaining vitamin D sufficiency. A study conducted among urban men in Pune, India also suggested that more than 1 h of casual midday sunlight exposure was necessary to maintain vitamin D levels [ 27 ]. In the present study, exposure of face, arms and legs to sunlight was associated protectively with VDI compared to exposure of face and arms alone.…”
Section: Discussionmentioning
confidence: 99%